From dissent to controversy: rhetorical-discursive strategies. A case study - Gil, Isabel Fuzeta (2020)
This study focuses on the analysis of some rhetorical-argumentative strategies and the textual and compositional configuration of discursive productions within the parliamentary political discourse, which generates agonism and a strong cleavage between parties. We specifically analysed the discourses on the referenda held in 1998 e 2007, concerning changes to the so-called “VIP law”. We established a corpus comprising 41 texts published in the press and 7 texts published in the Diário da Assembleia da República (containing written transcripts of the debates held in Parliament). We concluded that rhetorical-discursive strategies that highlight and deepen dissention are particularly relevant, particularly in the process of referencing “abortion”. The strategies used to reference the discursive object “abortion” are analysed from a discursive-pragmatical and rhetori-cal standpoint; the reference of “abortion” is at the centre of agonistic interactions and sustains the arguments presented by the two opposing groups. We draw on the work by Amossy (2012 [2000], 2014), Plantin (1996, 2011), Micheli (2008, 2011), Charaudeau (2005, 2017), Marques (2000, 2005) and Fonseca (1992, 1998).